KLIENTALISME DAN NOKEN: Studi Kasus Keterpilihan Anggota Dpr Ri Dari Partai Nasdem Dapil Papua Di Kabupaten Jayawijaya Pada Pemilu 2019 - OKTAVINA SATTU PASAU; ADITYA PERDANA (Universitas Halu Oleo, 2022)
This study wants to explain the use of clientelism in the general election in Papua that applies the noken system. The Noken system itself is an election system in which there are two ways. First, Noken as a substitute for the ballot box, and secondly, the choice of indigenous peoples will be represented by the Chief of the Tribe. The research method used in this study is a qualitative method through interviews with informants as primary data and literature studies as secondary data. The purpose of this study is to reveal that the clientelistic phenomenon does not only occur in elections with a one man, one vote system like elections in general, but it also occurs in the noken election system, either by the method of representation through tribal chiefs or using noken as a substitute for ballot boxes. The clientelism theory used is according to Aspinall and Barenschot, who see clientelism through three dimensions, namely the Network dimension, the Resource Dimension, and the Discretionary Control Dimension. This theory was then relevant to be used by Roberth Rouw because he used the Network dimension through proximity to Regional Heads and Tribal Heads to obtain the majority of indigenous people's votes, the Resource Dimension was also used to build communication through stone burning parties and Roberth Rouw used the Discretion Control Dimension to show his performance. to the public during his tenure so that during the 2019 Election, Roberth Rouw managed to get 170,848 votes in Jayawijaya Regency and managed to sit in the DPR RI